ナンキョク ノ セキセツ シリョウ ヲ モチイタ エル・チチョン カザン 1982ネン フンカ ニ トモナウ ニサンカイオウ ホウシュツリョウ ノ スイテイ - 河野, 美香; コウノ, ミカ; 日下部, 実; クサカベ, ミノル; 藤井, 理行; フジイ, ヨシユキ; Kohno, Mika; Kusakabe, Minoru; Fujii, Yoshiyuki (1998)
P(論文) 火山噴火に伴う大気中への硫黄放出量の推定方法の一つに, 極地方の氷床の硫酸堆積量に基づく方法がある。これは, 氷床に堆積した雪に含まれる火山性硫酸の量にスケーリングファクター(核実験により放出され成層圏を経て降下した放射性物質の広がり方に基づいて決められた, 成層圏を経由する物質運搬効率を地球上の任意の地点で与えるファクター)を乗じる方法である。ケーススタディとして, 近年の爆発的噴火の一つであるメキシコのエルチチョン火山1982年噴火について, 南極氷床のドームふじ雪試料から硫黄放出量を推定した。同噴火による放出量は, 人工衛星に搭載した紫外線分光器(TOMS)による噴煙のリモートセンシングにより推定されており(7Mt SO_2), 本研究による推定値はこれの2.5倍程度の値であった(17Mt SO_2)。このことは, 過去の大噴火に伴う硫黄放出量の推定に, 氷床の硫酸堆積量に基づく方法が適用できることを示している。 The SO_2 emission at the time of the 1982 eruption of El Chichon in Mexico was estimated by a glaciological method based on sulfate ion concentration and bomb-produced total β activity in snow collected in Antarctica. The glaciological estimate of the SO_2 emission is 17±1 Mt SO_2,somewhat greater than the spectroscopic estimate (7Mt SO_2) measured by a satellite-carried total ozone mapping system. We conclude that the glaciological method is useful to estimate SO_2 emissions of past explosive volcanic eruptions in the equatorial region. departmental bulletin paper